2018
DOI: 10.3389/fcimb.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening and Biomolecular Interactions of CviR-Based Quorum Sensing Inhibitors Against Chromobacterium violaceum

Abstract: The rise of bacterial multi drug resistance becomes a global threat to the mankind. Therefore it is essential to find out alternate strategies to fight against these “super bugs.” Quorum sensing (QS) is a cell-to-cell communication mechanism by which many bacteria regulate their biofilm and virulence factors expression to execute their pathogenesis. Hence, interfering the quorum sensing is an effective alternate strategy against various pathogens. In this study, we aimed to find out potential CviR-mediated quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…In our previous work [36], we have reported that C7X, sappanol and butein inhibited the QS mechanism in Chromobacterium violaceum. Though they might have different mode of interaction with CviR in C. violaceum from LasR in P. aeruginosa, their QS inhibition against both pathogenic bacteria implied that they might represent a broad spectrum anti-infective activity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous work [36], we have reported that C7X, sappanol and butein inhibited the QS mechanism in Chromobacterium violaceum. Though they might have different mode of interaction with CviR in C. violaceum from LasR in P. aeruginosa, their QS inhibition against both pathogenic bacteria implied that they might represent a broad spectrum anti-infective activity.…”
Section: Discussionmentioning
confidence: 87%
“…Biofilm formation was measured using the microtitre plate assay to study the efficacy of QSIs [36,39]. Briefly, overnight cultures of P. aeruginosa PAO1 (OD600 nm = 0.4) were added into 1 mL of fresh LB medium with QSIs in different concentrations (1, 10, and 100 µM).…”
Section: Biofilm Inhibition Assaymentioning
confidence: 99%
“…Moreover, QS molecules can vary within the Gram-negative species, suggesting that fingolimod may not act as a QSI against all Gram-negative bacteria [ 61 , 62 ]. On the other hand, the LuxI/LuxR homologs have been reported in more than 100 Gram-negative species and more than 200 species use AHLs as QS signals, which implies that fingolimod still has a broad QSI activity against Gram-negative bacteria [ 68 ]. Since QS control biofilm formation as well as the expression of many virulence and pathogenic factors, QSIs have been the subject of a lot of attention in recent years as a promising alternative strategy to fight biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Monolith Nano Temper (NT) 115 was used for measuring molecular interactions. Based on the fluorescence intensities that were determined through MST measurements, and then Kd values calculated (van den Bogaart et al, 2012;Batoulis et al, 2016;Vinothkannan Ravichandran et al, 2018).…”
Section: Detection Of Esculetin Binding To Proteinsmentioning
confidence: 99%